2022
DOI: 10.1016/j.amsu.2022.103302
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of childhood functional constipation and gastroesophageal reflux disease (GERD)

Abstract: Objective Functional constipation (FC) and Gastroesophageal Reflux Disease (GERD) are common gastrointestinal disorders in children. The aim of this study is to investigate the correlation between functional constipation and GERD in children. Methods In this cross-sectional study, a total of 82 children aged <16 years who referred to the pediatric gastroenterology clinic of (XXX) and were diagnosed with functional constipation according to ROME III criteria, and gastroe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Conventionally, it has been posited that GERD and constipation are two autonomous pathologies in gastroenterology. Nonetheless, an array of observational investigations [11] [12] [13] [14] [29] [30] has illuminated a potentially profound linkage between them, which is of paramount importance for devising nuanced diagnostic modalities and e cacious therapeutic interventions, thereby catalyzing extensive scholarly debate. However, the observational nature of these inquiries imposes constraints on our understanding of their relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventionally, it has been posited that GERD and constipation are two autonomous pathologies in gastroenterology. Nonetheless, an array of observational investigations [11] [12] [13] [14] [29] [30] has illuminated a potentially profound linkage between them, which is of paramount importance for devising nuanced diagnostic modalities and e cacious therapeutic interventions, thereby catalyzing extensive scholarly debate. However, the observational nature of these inquiries imposes constraints on our understanding of their relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, GERD and constipation have been perceived as discrete clinical entities within a medical canon. Nevertheless, an emergent corpus of evidence from longitudinal and cross-sectional research paradigms has revealed a notable con uence of these maladies [11]. The REACTION-J2 study [12] in Japan, which analyzed a cohort of 10,000 subjects using a spectrum of diagnostic criteria for both constipation and GERD, deduced from a multifaceted analysis across nine distinct criteria sets that the prevalence of constipation among individuals diagnosed with GERD markedly exceeded that of their non-GERD counterparts, with patients a icted by both conditions reporting a substantial degradation in quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…31 The correlation between GERD and FC found in this study aligns with prior research by Ahmadipour et al (2022), reinforcing the notion that these two conditions may have interconnected factors or pathways influencing their occurrence. 21 However, further investigation is needed to elucidate the underlying mechanisms and clinical implications of this relationship, which could potentially inform preventive and treatment strategies for individuals with these gastrointestinal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…19 In children, a combination of GERD and FC has been reported. 20,21 To the best of our knowledge, there have been few studies published globally about the overlap between GERD and constipation, and no published research has been undertaken in Saudi Arabia. This overlap is useful in the treatment of these diseases since GERD and constipation are common gastrointestinal diseases in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%